Reflections on Dimensions of Educational Change: Lessons from One School Using Design Thinking as a School Reform Process - Ellen MacCannell; Aron Rosenberg; Vanessa Gold (Canadian Society for Studies in Education, 2022)
The purpose of this paper is to share researcher reflections about a school's withdrawal from an educational change initiative that uses design thinking as a reform process. Upon reviewing audio-recorded workshop and debrief transcripts, observational field notes, and one follow-up telephone interview with a teacher-participant, the researchers generated some preliminary ideas about the school's decision to withdraw. Drawing on case study methodology to interpret this qualitative data, this paper comprises three nascent dimensions of educational change which align with extant academic discourses: direction of change, facilitation approach, and communication. We interweave researcher observations and participant perspectives to provide a snapshot of how one school using a design thinking-based reform process experienced approaching school change. Little research documents design thinking as a change process, let alone in a current reform initiative. This paper attends to this gap while also providing rare access to field experiences with design thinking in action